Ethics at the cinema - Jones, Ward E.; Vice, Samantha (Oxford ; New York : Oxford University Press, 2011)
The editors of Ethics at the Cinema invited a diverse group of moral philosophers and philosophers of film to engage with ethical issues raised within, or within the process of viewing, a single film of each contributor's choice. The result is a unique collection of considerable breadth. Discussions focus on both classic and modern films, and topics range from problems of traditional concern to philosophers (e.g. virtue, justice, and ideals) to problems of traditional concern to filmmakers (e.g. sexuality, social belonging, and cultural identity). --Book Jacket
Includes bibliographical references (p. 323-335) and index.
Keywords: Motion pictures -- Moral and ethical aspects